2008
DOI: 10.1375/twin.11.1.77
|View full text |Cite
|
Sign up to set email alerts
|

No Association of the Genetic Polymorphisms of Endothelial Nitric Oxide Synthase, Dimethylarginine Dimethylaminohydrolase, and Vascular Endothelial Growth Factor With Preeclampsia in Korean Populations

Abstract: T he purpose of this study was to investigate whether there is any association between preeclampsia and eNOS, DDAH, and VEGF gene polymorphisms, and also to search for a possible association between haplotypes in eNOS, DDHA, and VEGF genes and the risk for preeclampsia. DNA was extracted from whole blood of 223 preeclampsia patients and 237 healthy pregnant women. The genotypes were analyzed by a single base primer extension assay using a SNaPShot assay kit. Results were analyzed with the Student's t-test, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
(42 reference statements)
3
18
1
Order By: Relevance
“…Of those, seven studies were excluded (Kobashi et al, 2001;Grandone et al, 2003;Tempfer et al, 2004;Chen et al, 2007;Nishizawa et al, 2009;Singh et al, 2010;Sharma et al, 2011), because the distribution of the genotypes in the control group was not in HWE ( p < 0.05). Finally, 18 casecontrol studies were included in this meta-analysis (Yoshimura et al, , 2003Bashford et al, 2001;Tempfer et al, 2001;Hakli et al, 2003;Landau et al, 2004;Serrano et al, 2004;Hillermann et al, 2005;Fatini et al, 2006;Benedetto et al, 2007;Kim et al, 2008;Sandrim et al, 2008Sandrim et al, , 2010bSeremak-Mrozikiewicz et al, 2008;Aggarwal et al, 2010;Turan et al, 2010;Pappa et al, 2011;Salimi et al, 2011). All studies' characteristics and p-value for HWE from each study are listed in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of those, seven studies were excluded (Kobashi et al, 2001;Grandone et al, 2003;Tempfer et al, 2004;Chen et al, 2007;Nishizawa et al, 2009;Singh et al, 2010;Sharma et al, 2011), because the distribution of the genotypes in the control group was not in HWE ( p < 0.05). Finally, 18 casecontrol studies were included in this meta-analysis (Yoshimura et al, , 2003Bashford et al, 2001;Tempfer et al, 2001;Hakli et al, 2003;Landau et al, 2004;Serrano et al, 2004;Hillermann et al, 2005;Fatini et al, 2006;Benedetto et al, 2007;Kim et al, 2008;Sandrim et al, 2008Sandrim et al, , 2010bSeremak-Mrozikiewicz et al, 2008;Aggarwal et al, 2010;Turan et al, 2010;Pappa et al, 2011;Salimi et al, 2011). All studies' characteristics and p-value for HWE from each study are listed in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Thirteen genetic association studies of G894T polymorphism in preeclampsia involving 1488 cases and 2199 controls were included in the present meta-analysis (Table 2) (Yoshimura et al, , 2003Bashford et al, 2001;Tempfer et al, 2001;Hakli et al, 2003;Landau et al, 2004;Serrano et al, 2004;Hillermann et al, 2005;Fatini et al, 2006;Benedetto et al, 2007;Kim et al, 2008;Sandrim et al, 2008Sandrim et al, , 2010bAggarwal et al, 2010;Turan et al, 2010;Pappa et al, 2011;Seremak-Mrozikiewicz et al, 2011). Four of the 13 studies, were performed only in Asians (Yoshimura et al, , 2003Kim et al, 2008;Aggarwal et al, 2010), and 9 studies were conducted in non-Asians (Hakli et al, 2003;Landau et al, 2004;Serrano et al, 2004;Hillermann et al, 2005;Fatini et al, 2006;Sandrim et al, 2008Sandrim et al, , 2010bTuran et al, 2010;Pappa et al, 2011).…”
Section: Association Of the G894t (Glu298asp) Variant With Preeclampsiamentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, it has been observed that some genetic variants of eNOS gene may reduce baseline NO plasma levels [129]. Several casecontrols studies [130][131][132][133][134][135][136][137][138][139][140][141] have widely investigated the role in the pathophysiology of PE of the three most significant eNOS polymorphisms: 1) the T-786C, a single nucleotide polymorphism in the promoter region; 2) the intron 4 VNTR polymorphisms; 3) the variant in exon 7-G to T substitution at nucleotide position 894 in exon 7, resulting in the replacement of glutamic acid with aspartic acid at codon 298 (Glu298Asp). However, results of these investigations are conflicting and controversial.…”
Section: Genes Involved In Endothelial Dysfunctionmentioning
confidence: 99%